Preparation and characterisation of dielectric pyrochlores in the Bi2O3-mgo-M2O5 (M = Ta AND Nb) ternary systems - Tan, Phei Yi (2015)
A detailed and comprehensive investigation of synthesis and characterisation of the pyrochlores in the Bi2O3-MgO-Nb2O5 (BMN) and Bi2O3-MgO-Ta2O5 (BMT) ternary systems was presented. The structural flexibility and variable stoichiometry of these pyrochlore systems had given rise to many interesting properties. The excellent dielectric properties, e.g. low dielectric losses and high dielectric constants had rendered BMN and BMT pyrochlores as potential dielectric applications. Phase pure cubic pyrochlores in both BMN and BMT systems were successfully prepared using conventional solid-state method. As with phase diagram study, phase pure cubic pyrochlores in the Bi2O3-MgO-Nb2O5 system were found to form in a broad solution area whose compositions with bismuth content between 41.88 mole % and 44.50 mole %. The solid solution area was represented by an overall general formula of Bi3.36+xMg1.92-yNb2.72-x+yO13.76-x+(3/2)y, which used two variables with the associated limits of -0.01 ≤ x ≤ 0.20 and 0.00 ≤ y ≤ 0.16, respectively. On the other hand, pyrochlores in the Bi2O3-MgO-Ta2O5 system formed a relatively larger subsolidus solution area than that of the BMN system with the overall general formula Bi3.56-xMg1.96-yTa2.48+x+yO13.50+x+(3/2)y (0.00 ≤ x ≤ 0.32 and 0.00 ≤ y ≤ 0.20). Both BMN and BMT cubic pyrochlores were found to be thermally stable over a wide range of temperatures, i.e. 30 - 1000 °C. Selected BMN and BMT pyrochlores were characterised by AC impedance spectroscopy and these materials were found to exhibit excellent dielectric properties. High dielectric constants, ε’, low dielectric losses, tan δ in the order of 10-4 - 10-3 were recorded for BMN and BMT pyrochlores whose ε’ values were in the range of 167 - 204 and 70 - 85, respectively at temperature of 30 °C and frequency of 1 MHz. Both pyrochlores required high activation energies, Ea > 1.0 eV for their electrical conduction. The high activation energy suggesting that these materials were typical dielectric materials, which their conduction mechanism were governed by the hopping electronic type. Meanwhile, relaxor behaviour was observed for both systems in a low temperature range of 10 K - 320 K. The electrical data at low temperature range could be accurately fitted with different types of equivalent circuits, e.g. a parallel resistance-capacitance-constant phase element (R-C-CPE) element in series with a capacitor. In attempts to improve the electrical performance of the pyrochlore materials, chemical doping using divalent cations such as Ni2+, Cd2+ and Zn2+ cations was performed. Different solid solution limits were obtained and the results showed that dielectric constants and dielectric losses of divalent cations doped solid solutions did not vary significantly with increase of dopants concentration. On the other hand, pentavalent dopant, Nb5+ was introduced into BMT cubic pyrochlores using a formula of Bi3.50Mg1.80Ta2.70-xNbxO13.80 (0 ≤ x ≤ 2.70). It formed a complete substitutional solid solution and the dielectric constants were found to increase with increasing Nb5+ concentration. Nb doped BMT pyrochlores exhibited ε’ in the range of 81 - 195 and low dielectric loss of 0.0013 - 0.0059.